Design and evaluation of a novel hip prosthesis integrated with a truss system / Darshan Namasivayam - Darshan, Namasivayam (2021)
Post-operative fractures after a total hip arthroplasty (THA) are a major concern for patients. Among the factors contributing to the occurrence of these fractures are limiting fixation of the prosthesis, prosthesis stability as well as poor bone stock. Most postoperative fractures that occur after a THA are caused by the revision surgery due to prosthesis failure. Hence, implant design plays a major role in preventing such fractures. This study focuses on the design of a novel hip prosthesis that has the capability to distribute the stress through the prosthesis truss system without inducing additional stresses to the femur. The first stage of the study consisted of designing a novel prosthesis by varying three geometrical parameters namely truss angles, caput-collum-diaphyseal (CCD) angles and femur inclination angles to obtain a design with the best mechanical characteristics, i.e., the one that gives the lowest stress during typical dynamic activities such as walking, jogging, and cycling. From finite element simulation, it was found that the prosthesis design with the inclination angle of 20°, truss angle of 40° and CCD angle of 132.1° appears to give the lowest von Mises stress. The second stage of the study focused on evaluating the life cycle and safety factor of the proposed hip prosthesis that possessed the best characteristics. For this purpose, the maximum and minimum von Mises stresses at the critical location of prosthesis during each cycle of the dynamic activities are identified using finite element simulation. The Goodman relation is then used to estimate the prosthesis life cycle. The results show that the estimated lives were within an acceptable range. In the last stage of the work, the stress distributions in the femur during walking and jogging activities were evaluated. Two cases were investigated: (i) normal femur, i.e., the one without prosthesis and (ii) femur combined with the proposed prosthesis. Results showed that the addition of the proposed prosthesis reduced the stresses in the femur. These findings highlight the strength of the proposed prosthesis.